Study of crimes in the city of Kokand using GIS technologies and sociological questionnaires - Komilova, Nilufar; Makhmudov, Bakhodir; Latipov, Normurod (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. It is known that the influence of the demographic, social and economic conditions of the region on criminal activity is significantly high. In this place, researching the types of crime characteristic of cities with different functions, and identifying hotspots where criminal activity has intensified within the city will further enrich the scientific and practical aspects of the geography of crime. The use of geographic information systems (hereinafter GIS) in the implementation of these tasks is an important issue on the agenda of the field today. Analysis of recent research and publications. Today, in most developed countries, GIS is widely used to identify common crime areas and organize preventive measures for crime prevention. Research in this regard is almost undeveloped in the Republic of Uzbekistan. Formulation of the purpose of the article. In this study, theft and drug-related crimes committed in the city of Kokand, Fergana region, were investigated using the Hot Spot analysis method of the Arc GIS (version 10.8) program. The problems of combating crime in identified theft and drug-related crime centres were studied with the help of sociological surveys (conducted with prevention inspectors) and an action plan for crime prevention was developed. Presentation of the main research material. The indicators of crime levels in the small administrative areas of Kokand, in the Fergana region, have been examined in this study. In addition to the types of crimes that are most commonly committed in large social infrastructures (for example, markets, parks, public places) and their specific characteristics, we also discussed the levels of these types of crimes according to age, gender and population size. Problems and prospects of the development of crime geography in Kokand city. Hotspot analysis consists of identifying hotbeds of crime in the area and developing proposals and recommendations based on this. Proposals and recommendations for reducing crime in the city of Kokand. First, this technology is effective in identifying crime trends, organizing preventive measures, planning crime prevention strategies, and improving public safety. Second, GIS is adapted for data processing, mapping, and spatial analysis, thereby increasing the effectiveness of crime analysis and quickly creating a quality criminal analysis map. Thirdly, according to the results of this technology, optimization of the distribution of law enforcement officers, proper and planned deployment, and development of more effective crime reduction measures will help.